Sunlight-responsive tracking and monitoring system for solar panels - Abdul Haizul Faisal, Muhammad Dinie Imran; Mohd Saleh, Siti Aliyah; Sidik, Norbaiti; Abdul Jalil, Muhammad Farid (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Sunlight-Responsive Tracking and Monitoring System for Solar Panels is designed to optimize solar energy capture by dynamically aligning solar panels with sunlight intensity throughout the day. Using light-dependent resistors (LDRs), servo motors adjust the panels' orientation, ensuring maximum energy absorption. The system incorporates a voltage sensor for performance monitoring and a Wi-Fi-enabled ESP32 microcontroller for remote control and data visualization via the Blynk app. By automating sunlight tracking and integrating IoT capabilities, this system significantly improves energy efficiency, reduces manual intervention, and extends the lifespan of solar panels. Addressing common inefficiencies in static solar setups, this scalable solution is adaptable to various applications, including residential and industrial use. The project represents a sustainable approach to renewable energy utilization, contributing to global efforts to reduce reliance on non-renewable resources